Thematic studies on the Dead Sea scrolls - García Martínez, Florentino (Studies on the texts of the desert of Judah, 2007)
Brings together fourteen studies of Florentino Garcia Martinez on a variety of thematic topics from the ""Dead Sea Scrolls"", including English translations of essays that were hitherto only available in French or Spanish. The studies in this work range from essays on the interpretation of the biblical texts in the Scrolls, to more general studies.